Promovendo a Inclusão e o Acesso ao Conhecimento: Um Mecanismo de Busca Informado por Abordagem Semiótica em Redes Sociais - Reis, Julio Cesar dos; Baranauskas, M. Cecília C.; Bonacin, Rodrigo (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2012: Anais do XXV Concurso de Teses e Dissertações, 2012)
Due to the context of huge economical differences and cultural diversity in which we live, inclusive-oriented computational solutions and the access for all to the knowledge are essential. Search mechanisms in Social Networks Systems (SNS) could be an instrument for digital inclusion. However, the current search solutions have not yet been taking into account the language, and the semantic understanding shared by people in social networks. This dissertation developed the concept of “inclusive search” in SNSs, aiming at providing search results that make sense to ordinary people. The proposed approach is grounded on Organisational Semiotics, is empirically motivated by scenarios of use, and it was validated with real users. The dissertation is available at the UNICAMP digital library.